The Philosophical Foundations of Digital-Twin-Based IT Governance: A Philosophy-of-Science Perspective - Andi Agus Salim; Hasbu Naim Syaddad; Luki Ishwara; Agus Nursikuwagus; Usep Muhammad Ishaq; Andrias Darmayadi (JRSI (Jurnal Rekayasa Sistem dan Industri), 2026)
The increasing adoption of digital twins in organisational settings has extended their use beyond technical optimisation toward decision support and governance functions. However, existing studies on digital twin-based IT governance largely emphasise technical architectures and performance considerations, while paying limited attention to the philosophical assumptions that shape how these systems represent reality, generate knowledge, and influence decision-making. This paper addresses this gap by examining digital twin-based IT governance through a philosophy-of-science perspective. Drawing on concepts from ontology, epistemology, and scientific modelling, this study conceptualises digital twins as socio-technical artefacts that function simultaneously as models and interventions. The analysis demonstrates that digital twins embed specific assumptions about what constitutes organisational reality, what forms of knowledge are considered valid, and how governance actions are legitimised. These assumptions have direct implications for accountability, transparency, and human agency in IT governance processes. Based on this analysis, the paper articulates design implications for digital twin-based IT governance, highlighting the importance of interpretability, human-in-the-loop mechanisms, reflexive design, and value-sensitive approaches. Rather than offering empirical generalisations, the contribution of this paper is conceptual: it provides a structured analytical framework that clarifies the foundational assumptions underpinning governance-oriented digital twins. The paper concludes by outlining directions for future empirical and design-oriented research aimed at developing digital twin-based governance systems that are not only technologically effective but also epistemically robust and socially responsible